Efektivitas Pajak Karbon: Studi Literatur - Albab, Yufi Mohammad Ulil; Heru Tjaraka (Owner : Riset dan Jurnal Akuntansi, 2024)
Climate change is an issue that is being widely discussed internationally today. The aim of the research is to examine the effectiveness of carbon tax implementation and explain comprehensive results. This research method uses a systematic literature review of research conducted in the last 10 years. The search for the effectiveness of carbon tax as climate change mitigation then synthesizes the results of empirical studies that have been conducted. The researcher found that there are 3 things that should be of concern to the government; economic performance, industrial sector performance and social welfare. Carbon tax certainly has an effect on a country's economy, as carbon tax is basically imposed directly on products or services that cause emissions. many companies are burdened by the carbon tax because it will change the management of the company to use renewable energy. The price of products from the industry will also increase because the carbon tax is imposed directly on products that cause emissions. Welfare should be considered in the implementation of carbon tax by the government, as the policy will certainly have a negative effect on social welfare. The researcher found 3 things that should be the main consideration in planning and implementing the carbon tax policy itself, first is the macroeconomy, the industrial sector that contributes to social and macroeconomic and social welfare.